Molecular and micropropagation approaches for ex-situ conservation of boesenbergia stenophylla R. M. SM. - Toyat, Aicher Joseph (2017)
Jerangau Merah (Boesenbergia stenophylla) is highly endemic to the highland of Borneo. Due to its medicinal properties, it is highly sought which made their population declining. Rapid development and anthropogenic disturbance near the habitat may give negative impact on the Jerangau Merah population in their natural habitat. To date, there are no conservation strategies prepared for this species. Therefore a study was conducted to develop strategies to conserve this species which includes DNA profiling, DNA barcoding, micropropagation and nursery planting. A total of three natural locations of B. stenophylla were found in Bario, Ba’kelalan and Long Semadoh forest. Based on the DNA profiling with RAPD and SSRs markers there was no genetic variations found among sub populations from Bario. This finding implied that no variations may be caused to low hybridization because flowering is rare and propagation through rhizome is more dominant. DNA analysis using CpDNA and NrDNA markers showed that this species clades under the Borneo-Boesenbergia section. This proves further that this species is endemic and could not be found outside of Borneo. A micropropagation protocol was achieved for the in vitro cultures of B. stenophylla. It includes initial culturing using shoot tips in MS media containing 0.2 mg/L NAA for shoot induction followed by sub-culturing to MS media with 2 mg/L BAP + 0.4 mg/L NAA for rapid shoot elongation. B. stenophylla is highly endemic, having small populations, possibly lacks genetic variations and difficult to grow in in vitro cultures. The nursery studies show that the plant has it unique sympodial growth that proved that cannot be confined in the small polybag, so bedded planting was suggested for improving the growth in the nursery conditions. Therefore, this study suggests that their conservation should remain as in situ, seedlings production under optimum nursery conditions should be carried out near to their natural populations and further monitoring of new population occurrence for documentations.